2014
DOI: 10.1002/ajh.23655
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic stem cell transplantation as initial salvage for patients with acute myeloid leukemia refractory to high‐dose cytarabine‐based induction chemotherapy

Abstract: Purpose Outcomes of patients with acute myeloid leukemia (AML) who are refractory to high-dose Cytarabine (HiDAC)-based induction are dismal. Allogeneic hematopoietic stem cell transplantation (AHSCT) as initial salvage may be effective and potentially superior to conventional salvage chemotherapy. Methods Eighteen percent (285 of 1597) of AML patients were primary refractory to HiDAC-based regimens at the MD Anderson Cancer Center between 1995 and 2009. AHSCT was the initial salvage in 28 cases. These patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 15 publications
2
33
0
Order By: Relevance
“…Therefore, a new drug which resensitizes blasts to cytarabine may play a key role in future therapy. 21,22 When BCT-100 was combined with cytarabine, cytotoxicity that is greater than the sum of the 2 individual compounds alone was seen in AML samples (F (1,57) 5 6.405, P , .0001) ( Figure 3C). Analysis of individual patient samples showed that BCT-100 synergized with cytarabine (CI , 1) for almost all samples (Table 2).…”
Section: Bct-100 Reduces the Number Of Aml Blasts In Vitro And In Vivomentioning
confidence: 99%
“…Therefore, a new drug which resensitizes blasts to cytarabine may play a key role in future therapy. 21,22 When BCT-100 was combined with cytarabine, cytotoxicity that is greater than the sum of the 2 individual compounds alone was seen in AML samples (F (1,57) 5 6.405, P , .0001) ( Figure 3C). Analysis of individual patient samples showed that BCT-100 synergized with cytarabine (CI , 1) for almost all samples (Table 2).…”
Section: Bct-100 Reduces the Number Of Aml Blasts In Vitro And In Vivomentioning
confidence: 99%
“…222 Benefit may also be derived from allogeneic HCT in the presence of active disease, with CR2 achieved in 42% and long-term survival observed in 9% to 22%. [228][229][230][231] Another approach for patients with refractory or active disease is to use a short course of chemotherapy such as fludarabine, cytarabine, and amsacrine immediately prior to RIC and allogeneic HCT. With this approach, CR rates after allogeneic HCT of 70% to 90% are achieved, with expected 4-year survival ranging between 32% and 45%.…”
Section: Salvage Treatmentmentioning
confidence: 99%
“…In a more recent report from the MD Anderson Cancer Center, Jabbour et al 22 compared outcomes of 28 primary refractory AML patients who underwent an allogeneic HCT as initial salvage to 149 patients with primary refractory AML who received salvage chemotherapy alone. The 28 patients received grafts from: an HLA-matched sibling, n = 18; an HLA-matched unrelated donor, Abbreviations: BU = busulfan; CLO = clofarabine; DFS = disease-free survival; FLAMSA = fludarabine, cytarabine and amsacrine; HCT = hematopoietic cell transplantation; OS = overall survival; RIC = reduced-intensity conditioning.…”
Section: Primary Induction Failurementioning
confidence: 99%